2020
DOI: 10.1111/ibi.12872
|View full text |Cite
|
Sign up to set email alerts
|

A large‐scale survey of bird plumage colour aberrations reveals a collection bias in Internet‐mined photographs

Abstract: Birds with plumage colour aberrations are of interest to both the general public and scientists. However, due to their rarity in nature, information on the presence of colour aberrations is rarely found in the peer‐reviewed literature. Exploration of public observations using modern information technologies such as Internet‐based search engines could facilitate cost‐effective and rapid broad‐scale collection of data on phenotypic aberrations in animals but may also be prone to the same problems as fieldwork, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Nevertheless, the frequency of leucism in nightjars is close to the ones recorded for nocturnal mammals (bats) 9 . The smaller prevalence reported in most other bird studies could reflect a detection bias resulting from the use of indirect approaches, such as citizen science data and online search tools 21 . But, in any case, the direction of this bias should act to increase, rather than decrease, the actual frequencies of leucism, because rare plumage patterns tend to be overrepresented in non-systematic surveys and image repositories 21 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, the frequency of leucism in nightjars is close to the ones recorded for nocturnal mammals (bats) 9 . The smaller prevalence reported in most other bird studies could reflect a detection bias resulting from the use of indirect approaches, such as citizen science data and online search tools 21 . But, in any case, the direction of this bias should act to increase, rather than decrease, the actual frequencies of leucism, because rare plumage patterns tend to be overrepresented in non-systematic surveys and image repositories 21 .…”
Section: Discussionmentioning
confidence: 93%
“…The smaller prevalence reported in most other bird studies could reflect a detection bias resulting from the use of indirect approaches, such as citizen science data and online search tools 21 . But, in any case, the direction of this bias should act to increase, rather than decrease, the actual frequencies of leucism, because rare plumage patterns tend to be overrepresented in non-systematic surveys and image repositories 21 . Our estimates are unlikely to be confounded by such methodological bias, since they are based on the close examination of individuals captured during a systematic field-based survey.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, these sightings get a much more muted interest in the scientific literature (e.g., Schreiber et al 2006, Shawkey andHill 2006). The rise in community-driven science has made it possible to study these sightings in large numbers (Izquierdo et al 2018, Zbyryt et al 2021) in a way that is nearly impossible with museum holdings or an individual's own sightings alone. Here, we argue that viewing atypically colored birds through an evolutionary lens represents a unique opportunity to understand the evolution of plumage coloration in birds.…”
Section: Lay Summarymentioning
confidence: 99%
“…2018; Zbyryt et al . 2020). A study comparing urban and non‐urban areas in countries of Eurasia and Oceania found a higher number of leucistic individuals of the Eurasian blackbird ( Turdus merula ), the house sparrow ( Passer domesticus ) and the common starling ( Sturnus vulgaris ) in urban than in rural areas (Izquierdo et al .…”
Section: Bibliographic Analysismentioning
confidence: 99%